ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI HARGA SAHAM PADA PERUSAHAAN PERTAMBANGAN DI BURSA EFEK INDONESIA (Students' Journal of Accounting and Banking, 2014)
This study aims to determine the effect of ROI, EPS, DER, SIZE , and CR on stock prices of mining companies listed on the Indonesia Stock Exchange ( IDX ). The population is the entire mining companies in Indonesia Stock Exchange ( IDX ) the number of 66 companies and research over the period 2009 to 2011 . Samples taken in this study is as much 22perusahaan . The sampling technique used was purposive sampling . The analytical tool used in this study is Multiple Linear Regression Analysis. The results showed that the coefficient of determination in this study is the value of Adjusted R Square of 82.2 % . As for the statistical test of the F - test shows that, between ROI, EPS, DER, SIZE, and CR simultaneously affect the stock price . And partial hypothesis testing results show that there is a significant positive effect between ROI , EPS , and the SIZE of the stock price . As for DER, and CR positive effect was not significant. Keywords: Return On Investment, Earning Per Share, Debt To Equity Ratio, size, Current ratio end Stock Price